Prenatal exposure to di(2-ethylhexyl) phthalate disrupts ovarian function in a transgenerational manner in female mice†. Issue 1 (20th November 2017) - Rattan, Saniya; Brehm, Emily; Gao, Liying; Niermann, Sarah; Flaws, Jodi A
Abstract: Di(2-ethylhexyl) phthalate (DEHP) is a plasticizer found in polyvinyl chloride products such as vinyl flooring, plastic food containers, medical devices, and children's toys. DEHP is a ubiquitous environmental contaminant and is a known endocrine disrupting chemical. Little is known about the effects of prenatal DEHP exposure on the ovary and whether effects occur in subsequent generations. Thus, we tested the hypothesis that prenatal exposure to DEHP disrupts ovarian functions in the F1, F2, and F3 generations of female mice. To test this hypothesis, pregnant CD-1 mice were orally dosed with corn oil (vehicle control) or DEHP (20 and 200 μg/kg/day and 200, 500, and 750 mg/kg/day) daily from gestation day 10.5 until birth (7–28 dams/treatment group). F1 females were mated with untreated males to obtain the F2 generation, and F2 females were mated with untreated males to produce the F3 generation. On postnatal days 1, 8, 21, and 60, ovaries were collected and used for histological evaluation of follicle numbers and sera were used to measure progesterone, testosterone, 17β-estradiol, luteinizing hormone, and follicle stimulating hormone levels. In the F1 generation, prenatal exposure to DEHP disrupted body and organ weights, decreased folliculogenesis, and increased serum 17β-estradiol levels. In the F2 generation, exposure to DEHP decreased body and organ weights, dysregulated folliculogenesis, and disrupted serum progesterone levels. In the F3 generation, DEHP exposure accelerated folliculogenesis. These data suggest that prenatal exposure to DEHP leads to adverse multigenerational and transgenerational effects on ovarian function. Summary Sentence: Developmental exposure to di(2-ethylhexyl) phthalate adversely affects ovarian functions in multiple generations of mice.